Determination of the mechanical parameters of a bonded joint between a metal and a composite by comparing experiments with a finite-element model - Bernardin, Petr (Materiali in tehnologije, 2013)
The main goal of this work was to evaluate the application of a cohesive surface-based contact for bonded joints between rotational parts. The numerical simulations were realized using the commercial finite-element software Abaqus. The mechanical properties of the joint were identified using the gradient-optimization method implemented in the OptiSLang software. The identification was performed by minimizing the difference between the force-displacement diagram obtained from the numerical analyses and from the experiments. The shapes of the specimen and the bonded joint were designed in accordance with joints commonly used in the machine industry.
Keywords: joint; stik; vez; bond; composite; kompozit; kovina; metal; končni element; finite element; optimizacija; optimization; damage modelling; modeliranje poškodb; identification; identifikacija